/**
* { 0 i=1
* dp[i] = { dp[i-1]+2 i>1,pi[i-1]=i-1
* { dp[i-1]+(dp[i-1]-dp[pi[i-1]])+2 i>1,pi[i-1]<i-1
*/
import java.util.*;
public class Main{
public static void main(String[] args){
Scanner sc = new Scanner(System.in);
int n = sc.nextInt();
// 1-n
int[] pi = new int[n + 1];
// 1-(n+1)
long[] dp = new long[n + 2];
// 1-n
for(int i = 1; i <= n; ++i){
pi[i] = sc.nextInt();
}
sc.close();
long mod = (long)(1e9+7);
// 2-(n+1)
for(int i = 2; i <= n + 1; ++i){
if(pi[i - 1] == i - 1){
dp[i] = (dp[i - 1] + 2) % mod;
}else{
dp[i] = (dp[i - 1] + (dp[i - 1] - dp[pi[i - 1]]) + 2) % mod;
}
}
// System.out.println(Arrays.toString(dp));
System.out.println(dp[n + 1] < 0 ? dp[n + 1] + mod : dp[n + 1]);
}
}